Preparation method of efficient and stable TiNi alloy-based porous composite structure electro-catalysis electrode
By using TiNi alloy-based porous composite structure electrocatalytic electrode, combined with sodium metaaluminate pore-forming agent and dilute hydrochloric acid treatment technology, the problem that existing electrocatalytic electrodes cannot simultaneously have high hydrogen production efficiency, low cost and stable performance is achieved, and It has efficient, stable and economical hydrogen evolution catalytic effect.
Patent Information
- Application Number
- CN202411452413.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Existing hydrogen evolution electrocatalytic electrodes cannot simultaneously have high hydrogen production efficiency, low cost and excellent stable performance.
The porous composite structure electrocatalytic electrode with TiNi alloy as the substrate was used, and the Ti4Ni2O0.3, Ti4Ni2O0.6 and Ni3Ti layers with excellent conductivity and electrocatalytic activity were formed by treating sodium metaaluminate pore-forming agent and dilute hydrochloric acid solution.
The balance between cost and performance is achieved, significantly reducing the cost of the electrode, while improving hydrogen production efficiency and long-term service stability. The HER overpotential increased by only 7mV within 200h.
Smart Images

Figure CN119433596A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an electrocatalytic electrode. Background Art
[0002] In the context of global energy transformation, water electrolysis hydrogen production technology has a broad development space due to its environmental friendliness and simple process, and has become an important development direction of the future energy industry. Although hydrogen energy is highly praised for its clean and efficient characteristics, the high cost of electrode materials and electricity costs severely limit the widespread application of water electrolysis hydrogen production technology. Therefore, the development of efficient, stable and low-cost electrocatalysts is extremely important for the industrial application of water electrolysis hydrogen production. In recent years, researchers have made certain progress in the development of non-precious metal and trace precious metal electrocatalysts, but the stability of electrocatalysts is poor and cannot meet the long-term service activity requirements under working conditions. Therefore, it is urgent to design and develop electrocatalysts and preparation methods with high hydrogen production efficiency, low cost and outstanding stability. Summary of the invention
[0003] The present invention aims to solve the problem that the existing hydrogen evolution electrocatalytic electrode cannot have high hydrogen production efficiency, low cost and outstanding stability at the same time, and further provide a method for preparing an efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode.
[0004] A method for preparing an efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode is carried out according to the following steps:
[0005] 1. Pretreatment of sodium aluminate pore-forming agent:
[0006] ① Press the sodium aluminate powder into blocks, then sinter at high temperature in an air atmosphere, and finally take it out after cooling in the furnace to obtain sodium aluminate sintered blocks;
[0007] ② Grind and sieve the sodium aluminate sintered block to obtain sodium aluminate particles;
[0008] 2. Ball milling mixing:
[0009] The sodium aluminate particles and the metal powder are ball-milled to obtain a mixture;
[0010] The particle size of the metal powder is 10 μm to 50 μm;
[0011] 3. Preparation of porous TiNi-based alloys:
[0012] ① Place the mixed material in a graphite mold in a spark plasma sintering furnace, and pre-press it for 5 minutes to 15 minutes under a pressure of 30 MPa to 50 MPa to obtain a pre-pressed mixed material;
[0013] ② In vacuum or protective atmosphere, the pre-pressed mixture is heated to 1100°C to 1300°C, and kept at 1100°C to 1300°C for 10min to 20min, and finally cooled with the furnace to obtain a TiNi-based alloy block;
[0014] ③ Polishing the TiNi-based alloy block until the metallic luster is exposed to obtain a precursor;
[0015] 4. Composite of catalytic active layer:
[0016] ① Immerse the precursor in dilute hydrochloric acid, then place it in a high-frequency ultrasonic transducer, and oscillate for 5 minutes to 20 minutes at a frequency of 0.01kHz to 20kHz to obtain a precursor with a surface covered with catalytically active substances;
[0017] ② The precursor with the catalytically active substance on the surface is cleaned and dried, thereby completing the preparation method of the efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention uses abundant and low-priced non-precious metal materials as raw materials to prepare HER catalytic activity close to that of precious metal electrocatalysis, but the cost is much lower than that of precious metals such as Pt, Ir, and Ru, achieving a balance between cost and performance and showing significant economic benefits.
[0020] 2. The present invention can adjust the number of pores and pore size of the porous TiNi alloy obtained by sintering by controlling the amount of sodium aluminate and the particle size, thereby controlling the electrochemically active area. At the same time, the loading amount of the electrochemically active substance can be controlled by adjusting the concentration of hydrochloric acid and the action time of the ultrasonic transducer, thereby adjusting the effect on the HER catalytic performance. The preparation method is controllable.
[0021] 3. The electrode obtained by the present invention is based on a porous TiNi-based alloy, which has excellent thermodynamic stability and mechanical stability. The dilute hydrochloric acid solution reacts with the TiNi-based alloy and the sodium aluminate particle composite substrate, so that Ti4Ni2O with excellent conductivity and electrocatalytic activity is successfully grown on the surface of the porous TiNi alloy. 0.3 、Ti4Ni2O 0.6and Ni3Ti layer, all of which exhibit excellent electrical conductivity, providing a solid foundation for the electrode's excellent hydrogen evolution catalytic activity, thereby improving hydrogen production efficiency; this in situ grown electrocatalyst layer is firmly combined with the porous TiNi alloy substrate through chemical bonding, and the resulting catalyst layer presents a bulk morphology without obvious nanostructure, and has little effect on the morphology during long-term service, which makes it have excellent long-term service stability. Its HER overpotential only increases by 7 mV within 200 h, and it has broad application prospects.
[0022] 4. The water electrolysis catalytic electrode obtained by the present invention has a porous structure, which gives the electrode a high specific surface area; at the same time, the catalytic active substance on the electrode surface is an intermetallic compound with good conductivity, and the catalytic active substance layer on the electrode surface is firmly bonded to the porous TiNi-based alloy without the need for an organic adhesive, which significantly reduces the contact resistance and charge transfer resistance. The excellent conductivity and high specific surface area give it excellent catalytic activity. The TiNi alloy-based porous composite structure electrocatalytic electrode prepared by the present invention has a high specific surface area of 10 mA / cm 2 The lower overpotential is only 72 mV, which has excellent hydrogen evolution performance close to that of commercial Pt / C electrode (overpotential is 30 mV).
[0023] 5. The present invention can also be applied to other TiNi-based alloys for epitaxy, such as ternary or multi-element alloys such as TiNiFe, TiNiMo, TiNiCr and TiNiNb, and electrodes with excellent HER catalytic activity can be prepared by the method provided by the present invention.
[0024] Instruction Manual
[0025] Figure 1 This is a microscopic morphology of the precursor prepared in step 3③ of Example 1;
[0026] Figure 2 This is a microscopic morphology of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode prepared in Example 1;
[0027] Figure 3 The X-ray diffraction pattern of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode prepared in Example 1;
[0028] Figure 4 The electrochemical active area of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode and the commercial TiNi alloy prepared in Example 1;
[0029] Figure 5 HER polarization curves of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode and commercial 20% Pt / C prepared in Example 1;
[0030] Figure 6 This is a constant current stability test of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode prepared in Example 1 in 1M KOH electrolyte. DETAILED DESCRIPTION
[0031] Specific implementation method 1: This implementation method is a method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode, which is carried out according to the following steps:
[0032] 1. Pretreatment of sodium aluminate pore-forming agent:
[0033] ① Press the sodium aluminate powder into blocks, then sinter at high temperature in an air atmosphere, and finally take it out after cooling in the furnace to obtain sodium aluminate sintered blocks;
[0034] ② Grind and sieve the sodium aluminate sintered block to obtain sodium aluminate particles;
[0035] 2. Ball milling mixing:
[0036] The sodium aluminate particles and the metal powder are ball-milled to obtain a mixture;
[0037] The particle size of the metal powder is 10 μm to 50 μm;
[0038] 3. Preparation of porous TiNi-based alloys:
[0039] ① Place the mixed material in a graphite mold in a spark plasma sintering furnace, and pre-press it for 5 minutes to 15 minutes under a pressure of 30 MPa to 50 MPa to obtain a pre-pressed mixed material;
[0040] ② In vacuum or protective atmosphere, the pre-pressed mixture is heated to 1100°C to 1300°C, and kept at 1100°C to 1300°C for 10min to 20min, and finally cooled with the furnace to obtain a TiNi-based alloy block;
[0041] ③ Polishing the TiNi-based alloy block until the metallic luster is exposed to obtain a precursor;
[0042] 4. Composite of catalytic active layer:
[0043] ① Immerse the precursor in dilute hydrochloric acid, then place it in a high-frequency ultrasonic transducer, and oscillate for 5 minutes to 20 minutes at a frequency of 0.01kHz to 20kHz to obtain a precursor with a surface covered with catalytically active substances;
[0044] ② The precursor with the catalytically active substance on the surface is cleaned and dried, thereby completing the preparation method of the efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode.
[0045] Principle: Sodium aluminate (1650℃) with a higher melting point than TiNi alloy is used as a pore-forming agent, and a composite material of TiNi alloy and sodium aluminate particles is obtained by SPS spark plasma sintering as a precursor. Subsequently, the composite material of TiNi alloy and sodium aluminate particles is immersed in a dilute hydrochloric acid solution, and the sodium aluminate on the surface will dissolve into the solution, exposing the pore structure on the surface of the TiNi alloy, providing more abundant active sites for the hydrogen evolution reaction (HER) process; at the same time, since the Ti element in the TiNi alloy is more easily reacted with HCl, some Ti atoms on the surface of the TiNi alloy are dissolved by hydrochloric acid, so that the surface TiNi phase is transformed into a Ni3Ti phase with high catalytic activity and high conductivity; at the same time, sodium aluminate reacts with hydrochloric acid to produce basic aluminum chloride with strong electron capture ability, and basic aluminum chloride captures electrons in Ti2Ni, so that the Ti2Ni phase in the TiNi alloy is oxidized by basic aluminum chloride to generate Ti4Ni2O with good conductivity. x (Ti4Ni2O 0.3 、Ti4Ni2O 0.6 ). Highly catalytically active Ni3Ti and Ti4Ni2O x The synergistic effect enables the TiNi alloy-based porous composite structure electrocatalytic electrode to exhibit very excellent HER catalytic activity.
[0046] The beneficial effects of this embodiment are:
[0047] 1. This embodiment uses abundant and low-priced non-precious metal materials as raw materials to prepare HER catalytic activity close to that of precious metal electrocatalysis, but the cost is much lower than that of precious metals such as Pt, Ir, and Ru, achieving a balance between cost and performance and showing significant economic benefits.
[0048] 2. This embodiment can adjust the number of pores and pore size of the porous TiNi alloy obtained by sintering by controlling the dosage and particle size of sodium aluminate, thereby controlling the electrochemically active area. At the same time, the loading amount of the electrochemically active substance can be controlled by adjusting the concentration of hydrochloric acid and the action time of the ultrasonic transducer, thereby adjusting the effect on the HER catalytic performance. The preparation method is controllable.
[0049] 3. The electrode obtained in this embodiment is based on a porous TiNi-based alloy, which has excellent thermodynamic stability and mechanical stability. The dilute hydrochloric acid solution reacts with the TiNi-based alloy and the sodium aluminate particle composite substrate, so that Ti4Ni2O with excellent conductivity and electrocatalytic activity is successfully grown on the surface of the porous TiNi alloy. 0.3 、Ti4Ni2O 0.6and Ni3Ti layer, all of which exhibit excellent electrical conductivity, providing a solid foundation for the electrode's excellent hydrogen evolution catalytic activity, thereby improving hydrogen production efficiency; this in situ grown electrocatalyst layer is firmly combined with the porous TiNi alloy substrate through chemical bonding, and the resulting catalyst layer presents a bulk morphology without obvious nanostructure, and has little effect on the morphology during long-term service, which makes it have excellent long-term service stability. Its HER overpotential only increases by 7 mV within 200 h, and it has broad application prospects.
[0050] 4. The water electrolysis catalytic electrode obtained in this embodiment has a porous structure, which gives the electrode a high specific surface area; at the same time, the catalytic active substance on the electrode surface is an intermetallic compound with good conductivity, and the catalytic active substance layer on the electrode surface is firmly bonded to the porous TiNi-based alloy without the need for an organic adhesive, which significantly reduces the contact resistance and charge transfer resistance. The excellent conductivity and high specific surface area give it excellent catalytic activity. The TiNi alloy-based porous composite structure electrocatalytic electrode prepared in this embodiment has a high specific surface area of 10 mA / cm 2 The lower overpotential is only 72 mV, which has excellent hydrogen evolution performance close to that of commercial Pt / C electrode (overpotential is 30 mV).
[0051] 5. This embodiment can also be epitaxially extended to other TiNi-based alloys, such as ternary or multi-element alloys such as TiNiFe, TiNiMo, TiNiCr and TiNiNb, and electrodes with excellent HER catalytic activity can be prepared by the method provided in this embodiment.
[0052] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: Step 1 ① In an air atmosphere and at a temperature of 1000° C. to 1500° C., high-temperature sintering is performed for 3 h to 4 h. The rest is the same as the specific implementation method 1.
[0053] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the particle size of the sodium aluminate particles in step 1 ② is 100 μm to 300 μm. The rest is the same as specific implementation method 1 or 2.
[0054] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the volume ratio of the sodium aluminate particles to the metal powder in step 2 is (0.5-1.1): 1. The rest is the same as specific embodiments 1 to 3.
[0055] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that: the metal powder in step 2 is a mixture of Ti powder, Ni powder and other element powders; the other element powders are one or a combination of Fe powder, Mo powder, Cr powder and Nb powder; the atomic ratio of Ti:Ni:other elements in the mixture of Ti powder, Ni powder and other element powders is 1:1:(0-0.2). Others are the same as specific embodiments 1 to 4.
[0056] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the ball milling mixing described in step 2 is specifically carried out for 0.5h to 6h at a rotation speed of 300r / min to 500r / min and a ball-to-material ratio of (2 to 4):1. The rest is the same as specific embodiments 1 to 5.
[0057] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that the protective atmosphere in step 3② is a mixed atmosphere of Ar and H2, or the protective atmosphere is one or a mixture of Ar gas, N2 gas and He gas. The rest is the same as Specific embodiments 1 to 6.
[0058] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: in step 3②, the pre-pressed mixture is heated to 1100°C to 1300°C at a heating rate of 100°C / min to 200°C / min under vacuum or protective atmosphere. The rest is the same as specific embodiments 1 to 7.
[0059] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the concentration of the dilute hydrochloric acid in step 4① is 0.005 mol / L to 1 mol / L. The rest is the same as specific embodiments 1 to 8.
[0060] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the cleaning and drying described in step 4② is specifically performed in the following steps: cleaning with deionized water and ethanol in sequence, and then drying at a temperature of 25°C to 80°C. The rest is the same as specific embodiments 1 to 9.
[0061] The following examples are used to verify the beneficial effects of the present invention:
[0062] Embodiment 1:
[0063] A method for preparing an efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode is carried out according to the following steps:
[0064] 1. Pretreatment of sodium aluminate pore-forming agent:
[0065] ① Press the sodium aluminate powder into a block, then sinter it at a high temperature of 1500°C in an air atmosphere for 4 hours, and finally take it out after cooling in the furnace to obtain a sodium aluminate sintered block;
[0066] ② Grind and sieve the sodium aluminate sintered block to obtain sodium aluminate particles;
[0067] The particle size of the sodium aluminate particles is 150 μm to 300 μm;
[0068] 2. Ball milling mixing:
[0069] Under the conditions of a rotation speed of 300 r / min and a ball-to-material ratio of 2:1, the sodium aluminate particles and the metal powder were ball-milled for 2 h to obtain a mixture;
[0070] The particle size of the metal powder is 10 μm to 50 μm; the volume ratio of the sodium aluminate particles to the metal powder is 1:1; the metal powder is TiNi alloy powder; the atomic ratio of Ti:Ni in the TiNi alloy powder is 1:1;
[0071] 3. Preparation of porous TiNi-based alloys:
[0072] ① Place the mixed material in a graphite mold in a spark plasma sintering furnace, pre-press for 5 minutes at a pressure of 30 MPa to obtain a pre-pressed mixed material;
[0073] ② Under vacuum, the pre-pressed mixture is heated to 1200°C at a heating rate of 120°C / min, and kept at 1200°C for 10 minutes, and finally cooled with the furnace to obtain a TiNi-based alloy block;
[0074] ③ Use sandpaper to polish the TiNi-based alloy block until the metallic luster is exposed to obtain a precursor;
[0075] 4. Composite of catalytic active layer:
[0076] ① Immerse the precursor in dilute hydrochloric acid, then place it in a high-frequency ultrasonic transducer, and oscillate and react for 15 minutes at a frequency of 10 kHz to obtain a precursor with a surface covered with catalytically active substances;
[0077] The concentration of the dilute hydrochloric acid is 0.1 mol / L;
[0078] ② The precursor with the catalytic active substance on the surface is cleaned with deionized water and ethanol in turn, and then dried at a temperature of 60°C to obtain a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode.
[0079] Figure 1This is a microscopic morphology of the precursor prepared in step three (3) of embodiment one; it can be seen from the figure that there is a pore structure with a pore size of about 200μm to 300μm on the surface of the precursor, the pores are sodium aluminate pore-forming agent, and the relatively flat morphology outside the pores is TiNi alloy.
[0080] Figure 2 The microscopic morphology of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode prepared in Example 1; As can be seen from the figure, the catalyst layer on the electrode surface presents a bulk morphology without obvious nanomorphological features; The electrode surface presents a porous structure, which is due to the sodium aluminate on the surface dissolving in the solution, exposing the pore structure on the surface of the TiNi alloy, with a pore size of about 200 μm to 400 μm, and this porous structure gives the electrode a larger specific surface area, providing more active sites for the hydrogen evolution reaction process, thereby improving the catalytic performance of the hydrogen evolution reaction. And because when the TiNi alloy and sodium aluminate composite structure material are placed in a dilute hydrochloric acid solution, the sodium aluminate in the pores will dissolve in the solution and react with the TiNi alloy together with the hydrochloric acid and produce a catalyst layer on the surface, there is no large amount of TiNi element in the pores, and the generated active substances are less than the TINi alloy plane, so the catalytic active substances at the original pores are less than the TiNi alloy plane part, and a certain pore structure is still maintained.
[0081] Figure 3 The X-ray diffraction diagram of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode prepared in Example 1; as can be seen from the figure, the surface catalyst layer of the TiNi alloy-based porous composite structure electrocatalytic electrode is composed of Ti4Ni2O 0.3 、Ti4Ni2O 0.6 And intermetallic compounds such as Ni3Ti, all of which show excellent conductive properties, providing a solid foundation for the electrode's excellent hydrogen evolution catalytic activity.
[0082] In a three-electrode test system with a carbon rod as the counter electrode and a 1 mol / L KOH solution as the electrolyte, the electrocatalytic electrode undergoes hydrogen evolution reaction (HER).
[0083] Figure 4 The electrochemical active area of the highly efficient and stable TiNi alloy-based porous composite electrocatalytic electrode and the commercial TiNi alloy prepared in Example 1; as can be seen from the figure, the electrochemical active area of the TiNi alloy-based porous composite electrocatalytic electrode is 15.37 mF / cm 2 The electrochemical active area of commercial TiNi alloy is 0.11 mF / cm 2 Due to the presence of porous structure, the electrochemical active area of the TiNi alloy-based porous composite electrocatalytic electrode is much higher than that of commercial non-porous TiNi alloy.
[0084] Figure 5 HER polarization curves of the highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode and commercial 20% Pt / C prepared in Example 1; as can be seen from the figure, the TiNi alloy-based porous composite structure electrocatalytic electrode can achieve 10 mA / cm during the hydrogen evolution reaction (HER) with an overpotential of only 72 mV 2 of current density.
[0085] Figure 6 This is a constant current stability test of the highly efficient and stable TiNi alloy-based porous composite electrocatalytic electrode prepared in Example 1 in 1M KOH electrolyte. The catalyst exhibits excellent long-term service stability, with its HER overpotential increasing by only 7mV within 200h, and almost no significant performance degradation.
Claims
1. A method for preparing an efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode, characterized in that It is carried out in the following steps:
1. Pretreatment of sodium aluminate pore-forming agent: ① Press the sodium aluminate powder into blocks, then sinter at high temperature in an air atmosphere, and finally take it out after cooling in the furnace to obtain sodium aluminate sintered blocks; ② Grind and sieve the sodium aluminate sintered block to obtain sodium aluminate particles; 2. Ball milling mixing: The sodium aluminate particles are ball-milled and mixed with the metal powder to obtain a mixture; The particle size of the metal powder is 10 μm to 50 μm; 3. Preparation of porous TiNi-based alloys: ① Place the mixed material in a graphite mold in a spark plasma sintering furnace, and pre-press it for 5 minutes to 15 minutes under a pressure of 30 MPa to 50 MPa to obtain a pre-pressed mixed material; ② In vacuum or protective atmosphere, the pre-pressed mixture is heated to 1100°C to 1300°C, and kept at 1100°C to 1300°C for 10min to 20min, and finally cooled with the furnace to obtain a TiNi-based alloy block; ③ Polishing the TiNi-based alloy block until the metallic luster is exposed to obtain a precursor; 4. Composite of catalytic active layer: ① Immerse the precursor in dilute hydrochloric acid, then place it in a high-frequency ultrasonic transducer, and oscillate for 5 minutes to 20 minutes at a frequency of 0.01kHz to 20kHz to obtain a precursor with a surface covered with catalytically active substances; ② The precursor with the catalytically active substance on the surface is cleaned and dried, thereby completing the preparation method of the efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode.
2. The method for preparing a highly efficient and stable TiNi alloy-based porous composite electrocatalytic electrode according to claim 1, characterized in that Step 1① Sintering at high temperature for 3h to 4h in an air atmosphere at a temperature of 1000℃ to 1500℃.
3. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that The particle size of the sodium aluminate microparticles described in step 1② is 100 μm to 300 μm.
4. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that The volume ratio of the sodium aluminate particles to the metal powder described in step 2 is (0.5-1.1):
1.
5. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that The metal powder described in step 2 is a mixture of Ti powder, Ni powder and other element powders; the other element powders are one or a combination of Fe powder, Mo powder, Cr powder and Nb powder; the atomic ratio of Ti:Ni:other elements in the mixture of Ti powder, Ni powder and other element powders is 1:1:(0-0.2).
6. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that The ball milling mixing described in step 2 is specifically carried out for 0.5h to 6h at a rotation speed of 300r / min to 500r / min and a ball-to-material ratio of (2 to 4):
1.
7. The method for preparing a highly efficient and stable TiNi alloy-based porous composite electrocatalytic electrode according to claim 1, characterized in that The protective atmosphere described in step 3② is a mixed atmosphere of Ar and H2, or the protective atmosphere is one or a mixture of several of Ar gas, N2 gas and He gas.
8. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that In step 3②, the pre-pressed mixture is heated to 1100°C to 1300°C at a heating rate of 100°C / min to 200°C / min under vacuum or protective atmosphere.
9. The method for preparing a highly efficient and stable TiNi alloy-based porous composite electrocatalytic electrode according to claim 1, characterized in that The concentration of the dilute hydrochloric acid described in step 4① is 0.005mol / L~1mol / L.
10. The method for preparing a highly efficient and stable TiNi alloy-based porous composite structure electrocatalytic electrode according to claim 1, characterized in that The cleaning and drying described in step 4② are specifically carried out according to the following steps: cleaning with deionized water and ethanol in sequence, and then drying at a temperature of 25°C to 80°C.
Citation Information
Patent Citations
Preparation method of quasi-continuous pore nickel-manganese-gallium foam alloy
CN102719692A
Method for preparing nickel manganese gallium porous material provided with one-dimensional open pore by vacuum air pressure infiltration
CN103276233A
Porous high-entropy alloy and preparation method thereof
CN105624455A
Ni-Cu-Ti / CNTs porous composite material and preparation method thereof
CN113174513A
Production of titanium-nickel alloy sintered compact
JP1998088253A
Cited By
Application and preparation method of titanium-based intermetallic compound
CN122446242A